1989
DOI: 10.1073/pnas.86.17.6484
|View full text |Cite
|
Sign up to set email alerts
|

The alpha 3 beta 3 complex, the catalytic core of F1-ATPase.

Abstract: The a3.83 complex was reconstituted from a and (3 subunits of the thermophilic bacterium PS3 F1-ATPase (TFI) and then isolated. It is less stable at high and low temperatures than TFi?, and the complex dissociates into subunits during native polyacrylamide gel electrophoresis. The a_3%3 complex has about 20% of the ATPase activity of TF1. Its enzymic properties are similar to those of the native TFI, exhibiting similar cooperative kinetics as a function of ATP concentration, similar substrate specificity for n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
55
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(56 citation statements)
references
References 24 publications
1
55
0
Order By: Relevance
“…This mutant complex was expressed and purified in large amounts and responded to the ␥ C thiol modulation, but even its DTT-reduced MgATPase activity reached at the most 5 units/mg. Furthermore, no CaATPase activity has been reported in this mutant TF 1 -␣ 3 ␤ 3 ␥ complex, probably because in the native TF 1 , unlike in RrF 1 (Table I) and CF 1 (30), the CaATPase activity is 10-fold lower than its MgATPase activity (43).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This mutant complex was expressed and purified in large amounts and responded to the ␥ C thiol modulation, but even its DTT-reduced MgATPase activity reached at the most 5 units/mg. Furthermore, no CaATPase activity has been reported in this mutant TF 1 -␣ 3 ␤ 3 ␥ complex, probably because in the native TF 1 , unlike in RrF 1 (Table I) and CF 1 (30), the CaATPase activity is 10-fold lower than its MgATPase activity (43).…”
Section: Discussionmentioning
confidence: 96%
“…1). But in the TF 1 -␣ 3 ␤ 3 hexamers, which were assembled without AlF x , the CaATPase activity is 5-fold higher than their MgATPase, although the whole native TF 1 has a 10-fold lower Ca-than MgATPase activity (43). The specific inhibition of the RrF 1 -CaATPase by AlF x , which has not been tested on any other F 1 -CaATPase activity, provides an additional clear difference of functional properties of the RrF 1 -CaATPase and MgATPase activities.…”
Section: The Catalytic Properties Of the Isolated Rrf 1 Dimers Hexammentioning
confidence: 97%
“…The ␣ 3 ␤ 3 , ␣ 3 ␤ 3 ␥, and ␣ 3 ␤ 3 ␦ subcomplexes reconstituted from the isolated subunits of TF 1 1 are active as ATPases (3)(4)(5)(6). Both the ␣ 3 ␤ 3 and ␣ 3 ␤ 3 ␦ subcomplexes differ from TF 1 in that they are less specific for divalent cations and are insensitive to inhibition by azide (4,5). In contrast, the catalytic characteristics of the ␣ 3 ␤ 3 ␥ subcomplex are very similar to those of TF 1 (4,7,8).…”
mentioning
confidence: 99%
“…When separated from F 0 as a soluble complex, F 1 is composed of five different subunits in a stoichiometry of ␣ 3 ␤ 3 ␥␦⑀ and functions as an ATPase (2). The ␣ 3 ␤ 3 , ␣ 3 ␤ 3 ␥, and ␣ 3 ␤ 3 ␦ subcomplexes reconstituted from the isolated subunits of TF 1 1 are active as ATPases (3)(4)(5)(6). Both the ␣ 3 ␤ 3 and ␣ 3 ␤ 3 ␦ subcomplexes differ from TF 1 in that they are less specific for divalent cations and are insensitive to inhibition by azide (4,5).…”
mentioning
confidence: 99%
“…However, accumulating evidence has emerged to support the idea that the ␣ 3 ␤ 3 subcomplex can intrinsically catalyze cooperative ATP hydrolysis independently of ␥. Early studies have shown an assembled and catalytically active ␥-less complex in the thermophilic bacterium PS3 F 1 -ATPase (30,31). Genetic studies also supported the assembly of an active F 1 lacking ␥ in S. cerevisiae mitochondria (32).…”
Section: Discussionmentioning
confidence: 90%